Antifungal and enzymatic activities of endophytic fungi associated with Tamarix nilotica - Helal F. Al-Harthi (Plant Signaling & Behavior)
Fungal endophytes were recovered from Tamarix nilotica (Tamaricaceae) roots and stems collected in Taif, Saudi Arabia. A total of 49 different taxa were identified. The overall colonization rate of root and stem segments was 30.6%. A total of 49 isolates were collected and categorized into 21 operational taxonomic units using the rRNA gene’s internal transcribed spacer region. The most prevalent species were Penicillium chrysogenum (16 isolates), Fungal sp. (12), and Alternaria alternata (10). Forty-nine isolates were investigated for antifungal activity against Fusarium solani and Rhizoctonia solani; all tested isolates showed antifungal activity against Fusarium solani, while 43 isolates showed antifungal activity against Rhizoctonia solani. The most potent antifungal agents against Fusarium solani and Rhizoctonia solani are Aspergillus ochraceus (2 isolates) and Penicillium chrysogenum (16 isolates). Endophytic isolates collected during this experiment were evaluated to produce amylase, cellulase, lipase, and protease enzymes. Among the strains examined for enzymatic potentials (4 enzymes), 26 strains (53% of the total strains) produce only one enzyme. Penicillium chrysogenum (TUPc2, 3, and 4) produced the highest amount of the four enzymes that were examined.